2019
DOI: 10.1371/journal.pone.0214867
|View full text |Cite|
|
Sign up to set email alerts
|

ΔNp63 to TAp63 expression ratio as a potential molecular marker for cervical cancer prognosis

Abstract: p63 is a transcription factor p53 family. Two major isoforms of p63, TAp63 with transactivation (TA) domain and ΔNp63 with truncated TA domain, have been reported to play opposing roles either in tumor suppression or oncogenic function. Little is known about the association of these two isoforms of p63 in the carcinogenesis of cervical cancer. In this study, the mRNA expression levels of TAp63 and ΔNp63 in 40 normal, 30 low-grade squamous intraepithelial lesions (LSIL), 38 high-grade squamous intraepithelial l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…To investigate whether miR-944 interacts with p63 , which is the miR-944 host gene, the expression levels of two major isoforms of TAp63 and ΔNp63 mRNAs were compared with miR-944 expression levels. The mRNA expression levels of TAp63 and ΔNp63 were divided into negative and positive groups according to a cut-off value identified by receiver operator characteristic (ROC) curve analysis in normal and cervical cancer tissues [ 22 ]. Hence, the expression levels of miR-944 were compared in the TAp63 - and ΔNp63 -positive and negative groups.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To investigate whether miR-944 interacts with p63 , which is the miR-944 host gene, the expression levels of two major isoforms of TAp63 and ΔNp63 mRNAs were compared with miR-944 expression levels. The mRNA expression levels of TAp63 and ΔNp63 were divided into negative and positive groups according to a cut-off value identified by receiver operator characteristic (ROC) curve analysis in normal and cervical cancer tissues [ 22 ]. Hence, the expression levels of miR-944 were compared in the TAp63 - and ΔNp63 -positive and negative groups.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it was hypothesized that miR-944 may be functionally connected to its host gene, TP 63, especially ΔNp63 , in cervical cancer. Previous studies showed that ΔNp63 mRNA expression levels were significantly higher in the ME-180, SiHa, CaSki, and C33A cell lines than TAp63 mRNA expression levels and that miR-944 expression levels in ME-180, CaSki, and C4I were higher than those in other cervical cancer cell lines such as HeLa, SW756, and C33A [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…p63 is a transcription factor and a member of the same family as p53. Two isoforms of this protein have been identified, one with a normal transactivation domain and another, ΔNp63 with a truncated transactivation domain, and thus has an opposite function to that of p53, showing carcinogenic activity ( 115 ). miR-203 and ΔNp63 showed higher levels of expression in cervical tissues obtained from UCC compared with premalignant cervical lesions.…”
Section: The Role Of Ncrnas In Hpv-induced Uccmentioning
confidence: 99%
“…Gene targets of TAp63 and ΔNp63 are also partially different [18,24]. The distinction of ΔNp63 and TAp63 in clinical samples may be important because p63 expression patterns are associated with clinicopathological features of tumours and long-term prognosis [39,40]. ΔNp63 has a dominant-negative effect on p53 and p63 function [18] because it is able to functionally inactivate p53 [27].…”
Section: Introductionmentioning
confidence: 99%